Análisis de la deformación de las partículas de la arena del río Guamo por desgaste a través del equipo Micro – Deval. (2023)
This article presents the results of an experimental study that analyzes the effects of wear on the properties of sand from the Guamo river. The objective of the study was to evaluate the deformation of the sand particles of the Guamo river by wear through the Micro-Deval equipment, this is an equipment that is used to measure the abrasion resistance of the sands, it consists of a rotating drum containing steel spheres, these steel spheres are rubbed against the sand particles, which causes their wear.